Promoting Peri-urban Agriculture: A Remedy for Climate Change. Case of the Town of Delly Brahim in Algiers - Nesrine Bacha; Naima Hadj Mohamed (Environmental Science and Sustainable Development)
The issue of promoting peri-urban agriculture seems to be an important one in response to the various current concerns about the future of cities in the face of climate change. At first glance, these urban and peri-urban agricultural areas, which in the past served as a shelter for cities, are now threatened and increasingly losing their function of protecting urban areas from climatic hazards. This question is a priority when considering the future of agriculture in the context of urban expansion. We are therefore raising a number of concerns linked to multiple issues: significant reduction of land available for local agriculture, accelerated degradation of the city's natural environment, fragmentation of ecosystems, and deterioration of air and water quality.